2015
DOI: 10.1155/2015/652645
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Processed rGO/AgNPs/rGO Sandwich Structure as a Hole Extraction Layer for Polymer Solar Cells

Abstract: We found that inserting silver nanoparticles (AgNPs) between two layers of reduced grapheme oxide (rGO) has an effect on tailoring the work function of rGO. The utilization of rGO/AgNPs/rGO sandwich structure as the hole extraction layer in polymer solar cells is demonstrated. Solution-processable fabrication of this sandwich structure at the ITO/active layer interface facilitates the extraction of hole from active layer into ITO anode because of lowering the barrier level alignment at the interface. It result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Study of the role of AgNPs and polymers has been widely reported for many routes of synthesis and their applications [45,50,51]. Recently, AgNPs containing nanostructure nanocomposite have also been investigated for supercapacitors [52], polymer solar cells [53], or thin film silver-TiO 2 thermoelectric [54].…”
Section: By Comparing Figuresmentioning
confidence: 99%
“…Study of the role of AgNPs and polymers has been widely reported for many routes of synthesis and their applications [45,50,51]. Recently, AgNPs containing nanostructure nanocomposite have also been investigated for supercapacitors [52], polymer solar cells [53], or thin film silver-TiO 2 thermoelectric [54].…”
Section: By Comparing Figuresmentioning
confidence: 99%